Lusophone entrepreneurship: analysis of entrepreneurial behavioural characteristics in Brazilian and Portuguese universities - Locatelli, Débora Regina Schneider (2021)
This study analyzes the entrepreneurial characteristics of students from public universities. The objective was to evaluate the presence of the characteristics of entrepreneurship pointed out by McClelland through a comparative analysis between two countries and through an analysis using structural models. Data collection was performed with the questionnaire prepared by David McClelland that assesses entrepreneurial behavioural characteristics through 55 preliminary questions. Data were collected from 329 respondents at universities in Brazil and Portugal during 2019. A quantitative analysis was performed using AMOS 26 software, and structural equation models were tested for the three groups under analysis. The analysis resulted in the validation of three measurement models (Portuguese (PT) and Brazilian (BR), PT, and BR), and it was observed that all dimensions were relevant and statistically significant in the set of PT and BR simultaneously and in the BR group. For the PT group, only the dimension “taking calculated risks”, corresponding to H2, did not have statistical validity.